2003
DOI: 10.1063/1.1577228
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam generation in a diode with a gaseous plasma electron source I: Plasma source based on a hollow anode ignited by a multi-arc system

Abstract: We report on the operation of an electron diode with a cathode based on a hollow plasma anode (HPA) design. Six arc sources placed inside the anode cavity were used to produce a preliminary plasma. The latter was used to produce a high-current (up to 4 kA) gaseous discharge without formation of plasma spots at the anode wall and output grid. The plasma parameters inside the HPA were measured for different N2 and Xe gas pressures and discharge current amplitudes. It was found that the HPA operation is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We used an experimental setup similar to that described in refs. [3] and [4]. However, in the present case the HA was grounded and the collector was at high-voltage (HV) positive potential (see fig.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…We used an experimental setup similar to that described in refs. [3] and [4]. However, in the present case the HA was grounded and the collector was at high-voltage (HV) positive potential (see fig.…”
mentioning
confidence: 83%
“…One of the main advantages of the hollow-anode (HA) plasma source is that one can control the parameters of the plasma by changing the amplitude of the discharge current I d or the pressure inside the HA [1,2]. Our experiments with the HA [3][4][5] showed that the use of either an arc or a magnetron-like plasma source or a ferroelectric plasma source (FPS) allows one to achieve reliable ignition and sustainment of the discharge with amplitude of I d ≤ 4 kA and pulse duration of ∼ 2 × 10 −5 s at background pressure of P ∼ = 2 × 10 −2 Pa and without formation of plasma spots at the HA walls and at the HA output grid. It was found that the plasma acquires a positive potential of ≤ 40 V with respect to the HA and that the plasma density and electron temperature are n ≤ 10 13 cm −3 and T e ≤ 10 eV, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that continuous (of several microseconds) operation of the HA becomes possible owing to the formation of a dense plasma on the surface of the ferroelectric samples. This plasma formation can be considered a self-consistent process because of the absence of additional power supplies which are commonly used in cases of thermionic [5], multiple-arc and magnetron [4,6] electron sources. At present we do not know the exact mechanism of the continuous plasma formation.…”
Section: Discussionmentioning
confidence: 99%
“…This FPS-assisted HA plasma source served as a cathode in a diode generating electron beams with current amplitudes up to I b ≈ 1.5 kA and electron energies up to 300 keV [3]. It was shown that the FPS-assisted HA plasma source is the most efficient pulsed electron source among other investigated plasma sources owing to the high efficiency of electron beam extraction (I d ≈ I b ), the simplicity of the HA discharge ignition and its sustenance without the requirement of additional powerful sources of current and voltage [4][5][6]. It was found that the parameters of the generated electron beam (current amplitude and cross-sectional current density uniformity) depend on the parameters of the plasma produced by the HA.…”
Section: Introductionmentioning
confidence: 99%